Optimization of Barrel Vault Space Frame Model for Earthquake Resistant Structure: Optimasi Model Rangka Ruang Barrel Vault untuk Struktur Tahan Gempa - Oloan Johanes Siregar; Johannes Tarigan; Nursyamsi Nursyamsi (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Long-span buildings are essential in accommodating wide, unobstructed interior spaces, commonly applied in structures such as stadiums and assembly halls. Specific Background: One effective structural system for such buildings is the space truss with barrel vault configurations, known for their strength and spatial efficiency. Knowledge Gap: However, limited comparative studies exist on the seismic performance and material efficiency of various barrel vault space truss models. Aims: This study aims to analyze and optimize seven barrel vault space truss models spanning 192 m by 120 m with a height of 50 m, focusing on earthquake load response and structural tonnage. Results: The analysis reveals that model 1 has the lowest base shear (V = 3142.50 kN) and structural tonnage, while model 6 exhibits the highest tonnage—62.24% heavier than model 1—and base shear of 4881.18 kN. Novelty: The study provides a comparative seismic performance assessment of large-span space truss models under identical geometric and loading conditions. Implications: These findings support the structural optimization of space trusses for earthquake-prone regions, offering practical insights for efficient and resilient long-span building design. Highlights: Highlights the efficiency of barrel vault space trusses in seismic conditions. Compares seven models to determine the most optimal structure. Emphasizes material savings through structural optimization. Keywords: Space Truss, Earthquake Load, Structural Analysis, Barrel Vault, Optimization